Prospective monitoring of chronic myeloid leukemia patients from the time of TKI discontinuation: the fate of peripheral blood CD26+ leukemia stem cells - Pacelli, Paola; Santoni, Adele; Sicuranza, Anna; Abruzzese, Elisabetta; Giai, Valentina; Crugnola, Monica; Annunziata, Mario; Galimberti, Sara; Iurlo, Alessandra; Luciano, Luigiana; Sorà, Federica; Fava, Carmen; et al. (Frontiers in Pharmacology, 2023)
In Chronic Myeloid Leukemia (CML) about half of patients achieving a deep and stable molecular response with Tyrosine Kinase Inhibitors (TKIs) may discontinue TKI treatment without disease recurrence. As such, Treatment Free Remission (TFR) has become an ambitious goal of treatment. Given the evidence that deepness and duration of molecular response are necessary but not sufficient requisites for a successful TFR, additional biological criteria are needed to identify CML patients suitable for an efficacious discontinuation. Leukemia Stem Cells (LSCs) are supposed to be the reservoir of disease. Previously, we demonstrated that residual circulating CD34+/CD38-/CD26+ LSCs were still detectable in a consistent number of CML patient during TFR. In this study we explored the role of these cells and their correlation with molecular response in a cohort of 109 consecutive chronic phase-CML patients prospectively monitored from the time of TKI discontinuation. After a median observation time of 33 months from TKI discontinuation, 38/109 (35%) patients failed TFR, after a median time of 4 months, while 71/109 (65%) patients are still in TFR. At TKI discontinuation, peripheral blood CD26+LSCs were undetectable in 48/109 (44%) patients and detectable in 61/109 (56%). No statistically significant correlation between detectable/undetectable CD26+LSCs and rate of TFR loss was found (p=0.616). Correlating TKI therapy with incidence of TFR loss, imatinib treatment resulted statistically significant compared to nilotinib (p=0.039). Exploring the behavior of CD26+LSCs during TFR, we observed fluctuating values that were very variable between patients, and they resulted not predictive of TFR loss. Up to date, our results confirm that CD26+LSCs are detectable at time of TKI discontinuation and during TFR. Moreover, at least for the observation median time of the study the persistence of “fluctuating” values of residual CD26+LSCs do not hamper the possibility to maintain a stable TFR. On the contrary, even patients discontinuing TKI with undetectable CD26+LSCs could undergo TFR loss. Our results suggest other factors than residual LSCs “burden” playing an active role in controlling disease recurrence. Additional studies evaluating CD26+LSCs ability to modulate the immune system and their interaction in CML patients with very long stable TFR are ongoing.